The COVID-19 Pandemic and the Challenges of State Capacity in Education Policy - Fatkhuri Fatkhuri (FISIP UPNVJ, 2020)
Coronavirous Disease (COVID-19) outbreak has struck the globe including Indonesia. With the COVID-19 pandemic rapidly crawling, Government implements a Large-Scale Social Limitation (PSBB) in order to prevent the spread of COVID-19. In response to the COVID-19 pandemic, the Ministry of Education and Culture (MOEC) has boosted the transformation of educational institutions through the Learning From Home (LFH) policy. LFH is policy that concerns with serving students to conduct learning activities through the distance learning either via online or offline. The goal of this policy aims to mitigate the immediate impact of COVID-19 which rapidly spread across regions while at the same time Government can maintain the quality of learning process. Using the model of policy evaluation, this study assesses the LFH policy which is focused on the rooted causes contributed the ineffectiveness of the policy. As the COVID-19 pandemic becomes a critical challenge for Government, this study finds that the ineffectiveness of LFH is relied on some factors which obviously exacerbate the proper teaching and learning programs. These are including the incompetence of state (apparatus) resource which can be traced from the state perplexed to face the COVID-19 outbreak with no providing a comprehensive policy; the weak of a coordination between MOEC and other stakeholders both local government and private sectors, the infrastructure gap among regions particularly in the remote and rural areas, and less financial support for conducting LFH. These are becoming the huge problems during the Pandemic as these obviously impede the succeed of learning policy. Keywords: COVID-19, Policy, Learning, Government, Capacity